Multiple vitamin deficiencies in a patient with a history of chronic alcohol excess and self-neglect in the UK. (22nd September 2014) - Dickson, Jon Mark; Naylor, Greg; Colver, Graham; J Powers, Hilary; Masters, Paul
Abstract : We report a case of inadequate diet (caused by extreme self-neglect and alcohol excess) which led to chronic severe deficiencies of vitamins A, D and E. At presentation the patient had widespread follicular hyperkeratosis of the skin, keratomalacia of both eyes and a severe cognitive impairment. He responded well to treatment including high dose parenteral vitamins, but lasting impairments in his vision and cognition have caused permanent disability.